Notes on the correct identity of Ceratostylis siamensis (Epidendroideae: Podochileae) from India - Sarkar, Shuvadip (Universidad de Costa Rica, 2024)
While conducting taxonomic studies on the tribe Podochileae (Orchidaceae) for the Flora of India, two species, Ceratostylis siamensis and Ceratostylis himalaica have been examined using types, protologues, fresh specimens, and authentic herbarium collections. Ceratostylis siamensis was previously reported and documented in Arunachal Pradesh, India. However, we determined upon closer examination that this record was based on erroneous identification. The correct identity of this species is C. himalaica. Consequently, Ceratostylis siamensis is excluded from the flora of India.